IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DI SMP ISLAM AL-AZHAR 37 PEKANBARU - Putri, Lyindira (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2019)
School Based Management (SBM) is the alignment of resources which independently ran by schools where all stakeholder groups involved. SBM also provides a flexibility for schools to determine directions and policies that are relevant to the situation and environmental conditions. The purpose of this study was to determine the implementation of SBM in Islamic-Based Junior High Schools. This research was taken at Al-Azhar 37 Middle School in Pekanbaru. The research method that was qualitative research with a case study approach. The research subjects were the principal, student representatives, public relations representatives, administrative staff, and 2 teachers and 5 students. The research object was the implementation of school-based management it self. The data collection techniques used observation, interviews and documentation. As the results of this study, the authors found that several school policies were related to student management, school relationship management with the community, curriculum management, personal management, special service management, facilities and infrastructure management, school budget management. One of the policies that related to student management was providing the online registration of prospective new students as well as giving prospective students the terms and conditions It was continually completed by the requirements to do an interview, taking test of Math, English, Recitation and memorization test juz 30.